2004
DOI: 10.1200/jco.2004.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Directed Enzyme Prodrug Therapy: Intratumoral Administration of a Replication-Deficient Adenovirus Encoding Nitroreductase to Patients With Resectable Liver Cancer

Abstract: Direct intratumoral inoculation of CTL102 to patients with primary and secondary liver cancer is feasible and well tolerated. The high level of nitroreductase expression observed at 1 to 5 x 10(11) virus particles mandates further studies in patients with inoperable tumors who will receive CTL102 and CB1954.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 15 publications
0
79
0
3
Order By: Relevance
“…23 Clinical trials with NTR/CB1954 started in late 1990s when pharmacokinetics of CB1954 was tested in a phase I study on patients with primary and secondary liver tumors. 24 More recently, a replication-defective adenoviral vector CTL102 encoding gene has been used on patients with primary or secondary liver cancer 25 and prostate cancer. 8,26 However, there are many challenges yet to be overcome for it to be considered a robust therapy.…”
Section: Discussionmentioning
confidence: 99%
“…23 Clinical trials with NTR/CB1954 started in late 1990s when pharmacokinetics of CB1954 was tested in a phase I study on patients with primary and secondary liver tumors. 24 More recently, a replication-defective adenoviral vector CTL102 encoding gene has been used on patients with primary or secondary liver cancer 25 and prostate cancer. 8,26 However, there are many challenges yet to be overcome for it to be considered a robust therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, results of clinical trials have shown that, among other challenges, poor in vivo gene transfer efficiency poses a major obstacle for those approaches that rely on in vivo gene transfer into tumor cells. [1][2][3][4][5][6][7][8] This applies to 'suicide gene' therapy, oncogene antagonism, antiangiogenesis gene therapy and some forms of immunotherapy. Thus, intense efforts are being directed at modifying vectors and delivery systems in order to improve gene transfer.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] Dissemination into the circulation following IT injection has already been reported in both animal studies and clinical trials. [16][17][18] For example Wang et al (2006) 19 explored injecting 20 or 50 ml of adenovirus solution IT, using an infusion rate of 1.0 ml s À1 . With all injectate volumes there was considerable hepatic transduction, particularly at higher virus doses, implying shedding of viable virus from the tumour into the circulation although virus particle kinetics were not measured directly.…”
mentioning
confidence: 99%